Total hip replacement versus hemiarthroplasty in intracapsular fracture of the elderly - Aljizani, Ali; Baawad, Faris; Almaghrabi, Ahmad; Alshehri, Abdulsalam; Alhawash, Atif; Alzahrani, Jehad; Almashni, Riyadh; Aljabri, Nibras; Assiri, Abdullah; Alzaibak, Abdulah (International Journal Of Community Medicine And Public Health, 2018)
Hip fracture is common among elderly and it is considered a major public health problem. Total hip replacement and hemiarthroplasty are the procedures of choice for managing intracapsular hip fracture among this population. Each procedure has its advantages and disadvantages. Total hip replacement is generally more preferred because of its safety, efficacy, higher success rates, better early recovery, and lower need for operative revision. On the other hand, it is associated with higher dislocation rates and higher general complications. Hemiarthroplasty is another safe option for management of intracapsular hip fracture. It is associated with higher stability and lower dislocation rates. However, revision may be required postoperatively, and the functional outcomes are slightly lower. This article will review the literature evidence of the advantages and disadvantages of both total hip replacement and hemiarthroplasty.